Value of Marriage Reflected in Oscar Wilde's An Ideal Husband Drama (1895): A Feminist Perspective - Susanti, Dieta; , Dr. Phil. Dewi Candraningrum, S.Pd, M,Ed; , Titis Setyabudi S.S., M.Hum (2015)
The aim of this research is to show the value of marriage in An Ideal Husband drama by using feminist perspective. It is done by establishing two objectives: analyzing the drama based on its structural elements and analyzing the drama based on feminist analysis. This research is descriptive qualitative research. The object of the study is Oscar Wilde's An Ideal Husband (1895) drama published in 2006 by Pennsylvania State University. The data sources are divided into two namely primary data and secondary data. Primary data source is script of An Ideal Husband (1895) drama and the secondary data sources are other materials taken from books, journal, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusion. First, based on structural elements analysis, it shows that character and characterization, setting, plot, style, and theme are related to each other and form a unity. Second, based on feminist analysis, Oscar Wilde illustrates the lack of value of marriage in Victorian era which suffers the women. It is necessary to implement the value of marriage in marriage life and it must be done by husband and wife equally in order to have long last marriage.